CASE ANALYSIS OF RATNA SARUMPAET IN SPREADING FAKE NEWS FROM CRIMINAL LIABILITY PERSPECTIVE - Sakti Myharto, Wiend (IBLAM LAW REVIEW, 2021)
Ratna Sarumpaet lied to the public and to herself as if she was being mistreated by someone else which caused her face to become bruised. It was later discovered that it was the effect of plastic surgery. There are 2 formulations of the problems discussed including: 1) What is the criminal responsibility for the perpetrators of the crime of spreading false news? and 2) What is the responsibility for the fake news that Ratna Sarumpaet has committed? The research method used by the author is a normative juridical method, literature review which collects primary secondary and tertiary legal materials to be analyzed in perspective. There are two laws regulated in the Criminal Code in general and the ITE Law in particular in ensnaring Ratna Sarumpaet